2015
DOI: 10.1073/pnas.1517041113
|View full text |Cite
|
Sign up to set email alerts
|

The histone H2A deubiquitinase Usp16 regulates hematopoiesis and hematopoietic stem cell function

Abstract: Epigenetic mechanisms play important regulatory roles in hematopoiesis and hematopoietic stem cell (HSC) function. Subunits of polycomb repressive complex 1 (PRC1), the major histone H2A ubiquitin ligase, are critical for both normal and pathological hematopoiesis; however, it is unclear which of the several counteracting H2A deubiquitinases functions along with PRC1 to control H2A ubiquitination (ubH2A) level and regulates hematopoiesis in vivo. Here we investigated the function of Usp16 in mouse hematopoiesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…Several deubiquitinases, such as USP1, USP3, USP16, and A20, are reported to be essential for proper HSC functions (Gu et al., 2016, Lancini et al., 2014, Nagamachi et al., 2014, Nakagawa et al., 2015, Parmar et al., 2010). For example, a lack of A20 in mice leads to defective HSC quiescence and reduced HSC numbers caused by enhanced NF-κB activation (Nagamachi et al., 2014, Nakagawa et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several deubiquitinases, such as USP1, USP3, USP16, and A20, are reported to be essential for proper HSC functions (Gu et al., 2016, Lancini et al., 2014, Nagamachi et al., 2014, Nakagawa et al., 2015, Parmar et al., 2010). For example, a lack of A20 in mice leads to defective HSC quiescence and reduced HSC numbers caused by enhanced NF-κB activation (Nagamachi et al., 2014, Nakagawa et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent work demonstrated that deficiency in the histone H2A deubiquitinase MYSM1 results in a severe defect in the development of immune cells in mice and humans, outlining evolutionarily conserved mechanisms governing haematopoiesis in both species. [14][15][16][17] The work of our and several other groups indicated that MYSM1 regulates the maintenance of haematopoietic stem cells and their differentiation into B cells, natural killer cells, dendritic cells and erythrocytes. 7,11,12 MYSM1 is a chromatin-binding protein with deubiquitinase catalytic activity that has been shown to mediate the deubiquitination of lysine 119 of histone H2A.…”
Section: Introductionmentioning
confidence: 94%
“…13 Other histone H2A deubiquitinases such as USP16, USP21 and USP22 are known to influence B-cell and T-cell lymphopoiesis or lymphocyte activation. [14][15][16][17] The work of our and several other groups indicated that MYSM1 regulates the maintenance of haematopoietic stem cells and their differentiation into B cells, natural killer cells, dendritic cells and erythrocytes. 7,12,18,19 In this setting, MYSM1 exerts its role by controlling essential lineage-specific developmental regulators like Ebf1, Gfi1, Id2 and Flt3 at a transcriptional level.…”
Section: Introductionmentioning
confidence: 94%
“…USP16 is upregulated in Down’s syndrome (DS) cells due to extrachromosomal triplication in trisomy 21, downregulation of USP16 partially restores the impaired proliferation in DS somatic stem cells (Adorno et al, 2013). It has been reported that USP16 acts as a H2A DUB and regulates hematopoiesis and hematopoietic stem cell function (Gu et al, 2016). Moreover, USP16 is required for embryonic stem cell differentiation, where USP16 deficiency leads to embryonic lethality in mouse deletion models (Yang et al, 2014).…”
Section: Deubiquitinating Enzymesmentioning
confidence: 99%